A Legal Process in Cases of Domestic Violence Committed by TNI Personnel - Arief Fahmi Lubis (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2020)
The state considers that all forms of violence, especially domestic violence, constitute violations of human rights and crimes against human dignity. The objective of this study was to demonstrate that the integrity and harmony of a household can be disrupted if the quality and self-control cannot be maintained, ultimately leading to domestic violence and causing a sense of insecurity or injustice to those within the household. This qualitative research used a descriptive approach to systematically gather data that were factual and rapid in line with the condition when this study was conducted. The results showed that every individual within a household, in carrying out their rights and responsibilities, must be guided by religion. Such principles need to be nurtured and developed to build the integrity of a household.